环境温度变化对NGW行星轮系回差的影响 - 解晓辉; 宁广庆; 阳培 (Jixie chuandong)
The relationship between the total backlash in NGW planetary gear trains and backlash in gear pairs is derived. The equation for the calculation of backlash caused by ambient temperature change is also deduced. These results can provide necessary reference for relative engineering designs.